Dostoevsky : a writer in his time - Frank, Joseph, 1918-2013 (Princeton University Press, 2010)
Joseph Frank's award-winning, five-volume Dostoevsky is widely recognized as the best biography of the writer in any language--and one of the greatest literary biographies of the past half-century. Now Frank's monumental, 2500-page work has been skillfully abridged and condensed in this single, highly readable volume with a new preface by the author. Carefully preserving the original work's acclaimed narrative style and combination of biography, intellectual history, and literary criticism, Dostoevsky: A Writer in His Time illuminates the writer's works--from his first novel Poor Folk to Crime.